PENGARUH KUALITAS PELAYANAN DAN CITRA MEREK TERHADAP LOYALITAS PELANGGAN (Studi Pelanggan KFC Metrocity Pekanbaru) - Sinaga, Alfi Ranita; Sutrisna, Endang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This research was conducted at KFC Metrocity Pekanbaru, as for the purpose of this study was to determine the effect of service quality and brand image on customer loyalty (customer studies KFC Metrocity Pekanbaru). Quality of service (X1) and brand image (X2)as an independent variable while the customer loyalty as the dependent variable (Y).The problem in this study is the number of customers who experience fluctuations in Pekanbaru Metrocity KFC, and in the last 5 years only target achievment obtained in one year only in 2012. The samples were taken by 100 respondents from a population that is a calculated using slovin. Data obtained from the questionnaire and subsequently processed to then tested with statistics through SPSS.From the results of tests carried out showed that the quality of service and brand image positive and significant impact on customer loyalty in Pekanbaru Metrocity KFC of 41,7 %.Keywords: Quality of Service, Brand image, Customer Loyalty